Using Importance-Performance Analysis in The Measurement of Muslim Visitor's Satisfaction with Hotel Facilities in Taiwan - Siska Mandalia; Taufik Hidayat (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
Abstract Many countries in the world are considering tourism as an important sector in their economy. A rapid growth of Muslim population, in consequence increasing the number of Muslim travelers with their high contribution to global tourism revenue, has made Muslims a potential group of customers to the tourism market. Achieving Muslim tourist satisfaction could be very challenging for Non-Islamic Countries, especially Taiwan. To attract the Muslim visitors, Taiwan is eager to offer a Muslim friendly environment since Muslim people have some basic and specific needs in line with their belief and thispracticeis called Muslim travel or Halal tourism. Importance-Performance Analysis was conducted in this study to investigate which hotel attributes satisfy Muslim visitors and to identify their expectations and satisfaction with these attributes. The results indicated that “halal logo or certificate and its display at the entrance of hotel” had the strongest influence on Muslim visitor’s satisfactions with hotels in Taiwan. The results reported will enable hotels to better manage their facilities for Muslim visitors to ensure the sustainability of business performance.